DESCRIPTION OF POTASSIUM, NATRIUM AND NUTRITION AL STATUS IN ADULTS YOUNG HYPERTENSION PATIENS - Marianawati Saragih (Media Informasi, 2021)
Objective: to determine the description of potassium intake, sodium and nutritional status in young adults with hypertension. Method: using descriptive observational research design with survey approach. The variables measured in this study were sodium intake, potassium intake, nutritional status. Results: Potassium intake obtained in patients with hypertension was classified as less category, namely 71.8%. Sodium intake in patients with hypertension is mostly classified as lacking at 66.7%. The nutritional status of hypertensive patients in this study was 78.1% classified as obese. The conclusion of this study is that hypertension sufferers have begun to limit daily salt intake, but the nutritional status is still excessive, so there is a need for coaching from the local health center for weight management. Suggestions or recommendations in the form of potassium intake are still low so it is necessary to provide guidance regarding the intake of potassium, sodium in food. Thus the diet of hypertension sufferers will be more regular. Keywords: Potassium intake, hypertension, sodium, nutritional status